Population growth of Australian East coast humpback whales, observed from Cape Byron, 1998 to 2004 - Paton, David A.; Kniest, Rric (J. Cetacean Res. Manage., 2020)
Humpback whales (Megaptera novaeangliae) that migrate past the east coast of Australia comprise part of Group V (E(i) breeding stock). From 1995 to 2004 an annual 16 day survey was conducted from Cape Byron (28°37’S, 153°38’E), the most easterly point on the Australian mainland, monitoring the peak of the humpback whale northern migration. The annual rate of increase between 1998 and 2004 of humpback whales observed off Cape Byron is 11.0% (95% CI 2.3–20.5%). This rate of increase is consistent with that recorded from other studies of the humpback whale population off the east coast of Australia. The large confidence intervals associated with this estimate are due to considerable inter-annual variation in counts. The most likely explanation for this being the short survey period, which may not have always coincided with the peak of migration, and in some years a large proportion of whales passed Cape Byron at a greater distance out to sea, making sightability more difficult.